The psychology of philosophy: Associating philosophical views with psychological traits in professional philosophers - Yaden, David B.; Anderson, Derek E. (Philosophical psychology, 2021)
Do psychological traits predict philosophical views? We administered the PhilPapers Survey, created by David Bourget and David Chalmers, which consists of 30 views on central philosophical topics (e.g., epistemology, ethics, metaphysics, philosophy of mind, and philosophy of language) to a sample of professional philosophers (N = 314). We extended the PhilPapers survey to measure a number of psychological traits, such as personality, numeracy, well-being, lifestyle, and life experiences. We also included non-technical 'translations' of these views for eventual use in other populations. We found limited to no support for the notion that personality or demographics predict philosophical views. We did, however, find that some psychological traits were predictive of philosophical views, even after strict correction for multiple comparisons. Findings include: higher interest in numeracy predicted physicalism, naturalism, and consequentialism; lower levels of well-being and higher levels of mental illness predicted hard determinism; using substances such as psychedelics and marijuana predicted non-realist and subjectivist views of morality and aesthetics; having had a transformative or self-transcendent experience predicted theism and idealism. We discuss whether or not these empirical results have philosophical implications, while noting that 68% of our sample of professional philosophers indicated that such findings would indeed have philosophical value.